Uso de implantes com hormônio liberador de gonadotrofina em fêmeas e avaliação do sêmen durante a estação reprodutiva de pacu (Piaractus mesopotamicus) - Kuradomi, Rafael Yutaka [UNESP] (2013)
The aim of this study was to evaluate the possibility of ovarian maturation synchronization in a breeding herd of pacu (Piaractus mesopotamicus) by using slow-release implants with salmon gonadotropin releasing hormone analogue (sGnRHa). Furthermore, in addition of female's study, we evaluated the seminal characteristics throughout of the breeding season and the possibility of restripping. In this regard, females were implanted with sGnRHa pellets, and males were spermiated during of the breeding season and restripping were performed in males spermiated at the beginning and spermiated again at the middle of the season. To help in understanding the results, temporal variations between experimental groups of growth hormone (gh), luteinizing hormone beta subunit (lhb) and follicle-stimulating hormone beta subunit (fshb) gene expressions, and gonadal steroids concentrations were determined in males and females. In females, 35 days after pellets implantation (during the spawning period) the gene expression of lhb and fshb were increased in the treated and inhibited in the controls group, respectively, suggesting an lhb inducing effect by implant. In males, released milt volume increased throughout the breeding season, however, the indices related to sperm quality, especially to the DNA quality, were lower in the end than beginning of the season. The expressions of lhb, and gh were increased for the end season group against the reespermiado group, suggesting an association between gene expression and the maturation stage of the testes. Furthermore, the substantial increases of 11-ketotestosterone after hormonal induction in the beginning and restriping group correlated with good semen quality. We conclude that the using of implants may increases the frequency of the apt females in the spawning season. The using of semen at the end of the breeding season should be avoided and restripping is an alternative ...